The 'Tri Hita Karana' Ecotourism Approach For Sustainable Marine Resource Management and Tourism in Bali - Donny Juliandri Prihadi; Muhammad Raihan Shalahuddin; Evi Novianti; Nur Sakinah Junirahma; Wahyuniar Pamungkas; Ahmad Prawira Dhahiyat; Shafira Bilqis Annida; Ghulam M. Lahbar (International Journal of Marine Engineering Innovation and Research, 2024)
Marine ecotourism in Bali is vital for integrating environmental conservation, cultural preservation, and community empowerment. Despite its potential, sustainability efforts face significant challenges, including coral reef degradation, coastal erosion, marine pollution, and gaps in policy implementation. This study aims to evaluate the application of the Tri Hita Karana philosophy as a holistic framework to address these challenges in Bali’s marine ecotourism sector. A literature review method was used, synthesizing peer-reviewed studies, government reports, and case examples from major ecotourism sites such as Nusa Penida and Perancak Mangrove Forest. The results demonstrate that the Tri Hita Karana philosophy effectively integrates ecological, social, and cultural dimensions. Successful initiatives include coral reef restoration and community-based conservation programs that enhance biodiversity and support local economies. However, challenges such as inconsistent policy enforcement, visitor overcapacity, and infrastructure pressures remain significant. This study concludes that adaptive management strategies, including capacity assessments, collaborative governance, and technology integration, are essential to ensure the long-term sustainability of marine ecotourism in Bali. The findings contribute to the global discourse on sustainable tourism, offering Tri Hita Karana as a model adaptable to other culturally rich and ecologically sensitive regions.